(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2022)
René Girard, with his theories about sacrifice, mimetic desire and scapegoat, sought to understand society as it behaves in the midst of crisis and outside it, justifying rivalry and hatred for the model/rival. In this sense, it seeks to expose how these theories relate to current Brazilian society with regard to the LGBTQIPA+ social group.